Agribusiness Indicators : Zambia - World Bank (World Bank, Washington, DC, 2017)
Agriculture and agribusiness play an important role in the Zambian economy, contributing around 20 percent of gross domestic product (GDP) in recent years and about 12 percent of national export earnings. Agriculture employs nearly 70 percent of the labor force and remains the main source of income and employment for most of the people living in rural areas. The objective of the Zambia agribusiness indicators (ABI) country report is to examine factors that have affected agricultural productivity, market access, and the policy environment for agriculture in Zambia. This report presents findings of a data collection exercise carried out to compile a set of pilot ABI for Zambia. The pilot indicators presented are based on a review of the literature, government statistical bulletins, and primary interviews in the seed, fertilizer, mechanization, agricultural finance, and transport subsectors. The resulting indicators are presented in matrix form, together with notes indicating the specific data source (or sources) used for each indicator. A set of questionnaires was developed for this part of the exercise based on guidelines. Perception indicators on the quality of road infrastructure and other transport sector issues were added to supplement the checklist guidelines. The anticipated impact of the presentation of country performances will be to raise the competitiveness of African agriculture by bringing into sharper focus measures of how individual countries are transitioning towards a more commercial agriculture. This report consists of following seven chapters: chapter one gives introduction; chapter two presents access to and use of improved seed; chapter three focuses on fertilizer access and availability; chapter four focuses on access to farm machinery and tractor hire services; chapter five presents access to agricultural and agri-enterprise finance; chapter six gives cost and efficiency of transport in Zambia; and chapter seven presents policy and enabling environment for agribusiness development.